Pengembangan Diseminasi Official Statistics: Transformasi Digital dalam Layanan Statistik di Masa Pandemi Covid-19 - Dinar Sedah Arum Nian Sasirangan; Ambarari T; Stefanie Intan Christienova (Seminar Nasional Official Statistics, 2021)
According to Law No. 16 of 1997 on Statistics, BPS has an important role to provide trusted official statistics to the government and public. In practice, BPS consistently strives to improve and develop the quality of statistical public service. However, the Covid-19 pandemic has serious implications and poses challenges in various sectors, including the BPS statistical public service. It was previously carried out in several ways, such as direct visits, telephone calls, website, and SILASTIK. However, the enactment of the social activities restriction during the pandemic will affect offline statistical public service activities. Therefore, BPS adapts by making policy that optimize the use of information technology, namely by using online-based SILASTIK. The result showed a significant decrease during the pandemic in the type of direct visits service, where before the pandemic reached 25.3% then changed drastically to 6.5% of all types of services. In contrast to the online-based consulting services, which previously reached 21.8% increased to 37.6%. In line with the results, costumer ratings in SILASTIK and SKD results also show an increase in costumer satisfaction of BPS statistical service during the pandemic